Severity of deforestation mediates biotic homogenisation in an island archipelago. Issue 7 (18th May 2022) - Mitchell, Simon L.; Edwards, David P.; Martin, Rob W.; Deere, Nicolas J.; Voigt, Maria; Kastanya, Agustinus; Karja, Adi; Akbar, Panji Gusti; Jordan, Khaleb; Tasirin, John; Zakaria, Zuliyanto; Martin, Tom; et al.
Abstract : Anthropogenic‐driven species extinctions are radically changing the biosphere. Biological communities may become increasingly similar to or dissimilar from one another via the processes of biotic homogenisation or heterogenisation. A key question is how the conversion of native forests to agriculture may influence these processes by driving changes in the occurrence patterns of restricted‐range endemic species versus wide‐ranging generalists. We examined biotic homogenisation and heterogenisation in bird communities on the Southeast Asian islands of Borneo, Sulawesi, Seram, Buru, Talaud and Sangihe. Each island is characterised by high levels of avian endemism and unique spatial configuration of forest conversion to agriculture. Forest conversion to agriculture influenced the patterns of biotic homogenisation on five islands. Bird communities became increasingly dissimilar to forest reference communities relative to localised patterns of deforestation. Turnover led to species with larger global range‐sizes dominating communities at the expense of island endemics and ecological specialists. Within islands, forest conversion did not result in clear changes to β‐diversity, whereas between‐island communities became increasingly similar with greater deforestation, implying that patterns of forest conversion profoundly affect biotic homogenisation. Our findings elucidate how continued conversion of forests is causing the replacement of endemic species by a small cohort of shared ubiquitous species with potentially strong negative consequences for ecosystem functioning and resilience. Halting reorganisation of the biosphere via the loss of range‐restricted species and spread of wide‐ranged generalists will require improved efforts to reduce the impacts of deforestation, particularly in regions with high endemism.